2016
DOI: 10.1111/aas.12835
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life following trauma before and after implementation of a physician‐staffed helicopter

Abstract: Background: Implementation of a physician-staffed helicopter emergency medical service (PS-HEMS) in Denmark was associated with lower 30-day mortality in severely injured trauma patients and less time on social subsidy. However, the reduced 30-day mortality in severely injured patients might be at the expense of a worse functional outcome and quality of life (QoL) in those who survive. The aim of this study was to investigate the effect of a physician-staffed helicopter on long-term QoL in trauma patients. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…They found a slightly worse disability score for patients transported by PS‐HEMS. The two other studies measured quality of life using SF‐36 questionnaire that provides a Physical and Mental Summary score, and using EQ‐5D giving a measurement of health status . No differences between the groups in these two studies were found.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They found a slightly worse disability score for patients transported by PS‐HEMS. The two other studies measured quality of life using SF‐36 questionnaire that provides a Physical and Mental Summary score, and using EQ‐5D giving a measurement of health status . No differences between the groups in these two studies were found.…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in qualitative synthesis (n = 18) prospective, observational studies. Three types of patient categories were reported: 13 studies included trauma patients, [23][24][25][26][27][28][29][30][31][32][33][34][35] 5 studies included cardiac patients transported for primary percutaneous intervention 29,36-39 and 1 study included stroke patients. 40 One study, by Fjaeldstad et al, 29 included both trauma and cardiac patients.…”
Section: Includedmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent paper in Acta Anaesthesiologica Scandinavica examined quality of life in a group of trauma victims 4.5 years after injury 2. In this study, the physical component and the mental component of the SF‐36 questionnaire was employed.…”
mentioning
confidence: 99%